Melamine Trisulfonic Acid: An Efficient, Heterogeneous and Reusable Catalyst for the Synthesis of 10-Aryl-6,8-dimethyl- 6, 10-dihydro-5-oxa-6,8-diazaanthra [2,3-d][1,3]dioxole- 7,9-diones - Weilin Li; Qiuyan Luo (E-Journal of Chemistry)
Melamine trisulfonic acid was used as an efficient and recyclable catalyst for the one-pot synthesis of 10-aryl-6,8-dimethyl-6,10-dihydro-5-oxa-6,8-diazaanthra[2,3-d][1,3]dioxole-7,9-diones by condensation of 3,4-methylene dioxyphenol, aromatic aldehydes and 1,3-dimethylbarbituric acid under solvent-free conditions. Different types of aromatic. aldehydes were used in the reaction and in all cases the products were obtained in good to excellent yields.